The effect of outdoor and indoor group exercise classes on psychological stress in college students - Bramwell, Raeann Cay (Kansas State University, 2022)
Background: Stress is a detrimental external stimulus that can lead to illnesses and disease. College students especially are negatively affected by high levels of psychological stress which is a crucial time for them having new responsibilities. Exercise can be a mechanism for reducing stress, with outdoor group exercise potentially being a more beneficial opportunity to improve mental health compared to individual or indoor exercise. Purpose: This study tested the effects of outdoor compared to indoor group exercise classes on changes in perceived stress and outdoor physical activity in college students. The outdoor group was hypothesized to achieve more outdoor physical activity outside of the intervention and reduce their stress in a greater capacity compared to the indoor exercise group relative to baseline. Methods: Participants were recruited via email, paper flyers, university newsletter and indicated informed consent prior to participation in a four-week exercise intervention. Participants were randomized into hour-long outdoor (n = 7) or indoor (n = 6) group exercise classes held twice per week. Data were collected in October and November 2021 as pre (baseline), mid (after 4 exercise sessions), and post (after 8 exercise sessions) intervention surveys. Measurements included demographics, anthropometrics, perceived stress, and current physical activity behaviors. Mixed ANOVAs with Tukey post hoc tests were used to determine differences in perceived stress and outdoor physical activity levels between the indoor and outdoor exercise groups. Results: Participants (n = 13) were mostly aged 18-24 (76.9%), female (69.2%), and living off campus (69.2%). The largest group of particiapants were graduate students (38.5%) with the remainder spread evenly among grades (freshman, sohpmore, junior, senior). Adherence (attending at least 1 session) and measurement compliance (completing all time points) was low in the the outdoor group (n = 3 out of 7, 42.9%), while the indoor group was fairly high (n = 5 out of 6, 83.3%). Statistically significant differences in perceived stress scores existed across time for the whole sample (F (2, 12) = 48.359, p < 0.001, Partial Eta squared = 0.890) and the interaction between time and condition (F (2, 12) = 10.051, p = 0.003, Partial Eta squared = 0.626). With the posthoc analysis, the outdoor group (p < 0.001) showed a greater reduction in perceived stress from pre to post compared to the indoor group (p = 0.028). No significant outdoor physical activity differences were found between the interaction of time and condition (F (2, 12) = 0.948, p = 0.415, Partial Eta squared = 0.136). Conclusion: The first hypothesis was supported in that participants in the outdoor group significantly reduced their perceived stress more than the indoor group relative to baseline. However, the outdoor group did not engage in greater amounts of outdoor physical activity compared to the indoor group relative to baseline. University recreation facilities should work to establish reasonable outdoor space to facilitate outdoor group exercise classes. Future studies should look deeper into the elements of the outdoor environment that promote reductions in perceived stress and increase outdoor activity.
Keywords: Perceived stress; Outdoor exercise; College students